# 157aq1 - UNIVERSITY OF CALIFORNIA, DAVIS Department of...

This preview shows pages 1–3. Sign up to view the full content.

UNIVERSITY OF CALIFORNIA, DAVIS Department of Electrical and Computer Engineering EEC 157A CONTROL SYSTEMS QUIZ 1 FALL 2005 80 Minutes; Closed Book; 2 pages of notes allowed NAME : ALL PROBLEMS ARE BASED ON THE UNITY-FEEDBACK CONTROL SYSTEM: - R ( s ) + - h - E ( s ) C ( s ) - P ( s ) - Y ( s ) 6 input: r ( t ) , output: y ( t ) error: e ( t ) = r ( t ) - y ( t ) input-output transfer-function: H yr ( s ) = Y ( s ) R ( s ) input-error transfer-function: H er ( s ) = E ( s ) R ( s ) Problem 1 (25 points): The closed-loop step-response is y ( t ) = 0 . 2 - 0 . 6 e - 5 t +0 . 4 e - 6 t , t 0. a) What is the transfer-function H yr ( s ) ? b) Is the system BIBO stable? c) What is the steady-state error e ss due to a unit-step input? a) step-response is given, therefore, R ( s ) = 1 s Y ( s ) = 0 . 2 s - 0 . 6 s + 5 + 0 . 4 s + 6 = 0 . 6 s + 6 s ( s + 5)( s + 6) = H yr ( s ) = Y ( s ) R ( s ) = sY ( s ) = 0 . 6 s + 6 ( s + 5)( s + 6) b) the transfer function H yr is proper and has poles at - 5 , - 6, both in the open left-half-plane . Therefore, BIBO stable. c) E ( s ) = R ( s ) - Y ( s ) = 1 s - 0 . 6 s + 6 s ( s + 5)( s + 6) = s 2 + 10 . 4 s + 24 s ( s + 5)( s + 6) can use Final Value Theorem since system is BIBO stable. e ss = lim t →∞ e ( t ) = lim s 0 sE ( s ) = lim s 0 s s 2 + 10 . 4 s + 24 s ( s + 5)( s + 6) = 4 / 5 alternately, you can ﬁnd y ss y ss = lim t →∞ y ( t ) = lim s 0 sY ( s ) = lim s 0 s 0 . 6 s + 6 s ( s + 5)( s + 6) = 1 / 5 and e ss = 1 - y ss = 4 / 5 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Problem 2 (25 points): The input-output transfer-function is H yr ( s ) = 5 s + 10 s 3 + 4 s 2 + 3 s + 10 . a) What is the steady-state step-response y ss ? b) What is the input-error transfer function H er ( s ) ? c) What is the steady-state error due to a unit-ramp input? d) What is the type of this system? a) y ss = lim t →∞ y ( t ) = lim s 0 sY ( s ) = lim s 0 sH yr ( s ) R ( s ) = lim s 0 s 5 s + 10 s 3 + 4 s 2 + 3 s + 10 · 1 s = 1 b) E ( s ) = R ( s ) - Y ( s ) = H er ( s ) = 1 - H yr ( s ) = 1 - 5 s + 10 s 3 + 4 s 2 + 3 s
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 06/23/2008 for the course ECE 157A taught by Professor Chang during the Spring '08 term at Case Western.

### Page1 / 5

157aq1 - UNIVERSITY OF CALIFORNIA, DAVIS Department of...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online